GLS and GLS2 Glutaminase Isoenzymes in the Antioxidant System of Cancer Cells. - De los Santos-Jiménez, Juan; Campos-Sandoval, José Ángel; Alonso-Carrión, Francisco José; Márquez-Gómez, Javier; Mates-Sánchez, José Manuel (MDPI, 2024)
A pathway frequently altered in cancer is glutaminolysis, whereby glutaminase (GA) catalyzes the main step as follows: the deamidation of glutamine to form glutamate and ammonium. There are two types of GA isozymes, named GLS and GLS2, which differ considerably in their expression patterns and can even perform opposing roles in cancer. GLS correlates with tumor growth and proliferation, while GLS2 can function as a context-dependent tumor suppressor. However, both isoenzymes have been described as essential molecules handling oxidant stress because of their involvement in glutathione production. We reviewed the literature to highlight the critical roles of GLS and GLS2 in restraining ROS and regulating both cellular signaling and metabolic stress due to their function as indirect antioxidant enzymes, as well as by modulating both reductive carboxylation and ferroptosis. Blocking GA activity appears to be a potential strategy in the dual activation of ferroptosis and inhibition of cancer cell growth in a ROS-mediated mechanism.
Keywords: Isoenzimas; Estrés oxidativo; Células - Metabolismo; Cáncer - Aspectos moleculares; Cancer; Ferroptosis; Glutaminase; Glutaminolysis; Glutathione; Metabolic reprogramming; Oxidative stress; ROS